Leukocyte-Rich Platelet-Rich Plasma’s Clinical Effectiveness in Arthroscopic Rotator Cuff Repair: A Meta-Analysis of Randomized Controlled Trials - Peiyuan Tang; Meihui Huang; Wenfeng Xiao; Ting Wen; Pavel Volotovsky; Mikhail Gerasimenko; Shiyao Chu; Shuguang Liu; Kai Zhang; Yusheng Li (Bioengineering)
Background: Arthroscopic rotator cuff repair faces high retear risks in multi-tendon injuries due to insufficient biological healing; leukocyte-rich PRP may enhance tendon–bone integration through inflammatory modulation and growth factor release. Methods: Four databases including PubMed, Embase, Cochrane Library, and Web of Science were searched until March 2025. Literature screening, quality evaluation, and data extraction were performed according to inclusion and exclusion criteria. GRADE was used to grade the strength of the evidence and the results. Results: The main finding of this study was that leukocyte-rich platelet-rich plasma combined with arthroscopic surgery for rotator cuff injuries can improve the Constant Score (MD = 1.13, 95% CI: 0.19, 2.07, p = 0.02, I2 = 47%), American Shoulder and Elbow Surgeons score (MD = 6.02, 95% CI: 4.67, 7.36, p < 0.01, I2 = 0%), and University of California, Los Angeles score (MD = 1.20, 95% CI: 0.34, 2.06, p < 0.01, I2 = 0%) of patients with rotator cuff tear after treatment, and reduce the postoperative Visual Analog Scale score (MD = −0.62, 95% CI: −1.16, −0.08, p = 0.02, I2 = 83%) of patients. However, there were no statistical differences regarding the Simple Shoulder Test (MD = 0.08, 95% CI: −0.23, 0.39, p = 0.61, I2 = 5%). Conclusions: Based on current evidence, the use of LR-PRP in arthroscopic rotator cuff repair could lessen postoperative pain and improve postoperative functional scores in individuals with rotator cuff injuries.